(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Stroke is a major cause of mortality and long-term disability worldwide and is frequently associated with cardiovascular abnormalities. Electrocardiographic (ECG) and echocardiographic changes are commonly observed in acute stroke patients and may influence prognosis and clinical outcomes. This study aimed to evaluate ECG and echocardiographic abnormalities in patients with stroke. Methodology: This hospital-based observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2025 to December 2025. A total of 100 patients aged above 18 years with clinically and radiologically confirmed stroke were included. Detailed clinical evaluation, 12-lead ECG, and two-dimensional echocardiography were performed in all patients. Statistical analysis was carried out using SPSS version 25.0, and p <0.05 was considered statistically significant. Results: Among 100 stroke patients, 63 had ischemic stroke and 37 had hemorrhagic stroke. Abnormal ECG findings were observed in 90% of patients, while abnormal 2D-echocardiographic findings were present in 87% of patients. ST depression with T-wave inversion (16%) was the most common ECG abnormality, followed by QTc prolongation (12%) and atrial fibrillation (10%). Left ventricular hypertrophy with grade I diastolic dysfunction (44%) was the most common echocardiographic finding. Cardiovascular abnormalities were more frequent in hemorrhagic stroke patients, though statistically insignificant. Conclusion: ECG and echocardiographic abnormalities are highly prevalent in stroke patients. Routine cardiac evaluation may help in early diagnosis, risk stratification, and improved management of stroke-related cardiovascular complications.